Optical diffusers based on uniform nano-sized polymer balls/nematic liquid crystals composite films. Issue 5 (8th April 2020) - Zhou, Le; Saeed, Mohsin Hassan; Zhang, Lanying
ABSTRACT: Optical diffusers are promising diffusing materials in the optical devices such as monitors, projectors, fibre optics, light-emitting diode (LED) systems and liquid crystal displays (LCDs). We report optical diffusers comprising uniformly distributed nano-sized polymer balls/nematic liquid crystals (LCs) by ultraviolet (UV) click reaction of ene monomer and thiol monomer. By optimising the mass ratio 1:1 of ene and thiol, of which the average diameter of the corresponding nano-sized polymer balls is about 900 nm, relatively high optical transmission and haze with 88.99% and 94.49% are yielded, respectively. Furthermore, by controlling the curing time, the average diameter of nano-sized polymer balls can be reduced to 810 nm, and the developed film exhibits high transmission (98.49%) without sacrificing the high haze (91.77%). This paper demonstrates that UV click reaction is an economical approach to fabricate optical diffusers in a controllable manner. GRAPHICAL ABSTRACT: The nano-sized polymer balls' microstructure in the LCs/polymer composite films not only provide the optical diffuser with high transmission and high haze, but the optical properties of the optical diffuser are changed with the varied size of nano polymer balls. Additionally, the nano-sized polymer balls' morphology is controlled via ene-thiol click reaction, which has great potential in the applications of LCs/polymer composite films.